Developing sustainable geotourism as post-mining land use programs in Indonesia - Rohaendi, Nendi; Herlinawati, Herlinawati (Brawijaya University, 2024)
The development of sustainable geotourism as a post-mining land use alternative has become a popular issue in Indonesia. The geological and mining heritage will attract people with different kinds of interests and encourage the development of tourism. The paper analyzed technical, economic, social, and mine site factors that contribute to the development of post-mining land use programs. The paper focuses on the developing criteria or aspects that should be taken into account for developing the geological and mining heritage to integrate the environment of geopark in the future. The Analytical Hierarchy Process (AHP) method is applied to measure the importance of the aspect. The results show that the economic aspect is very important to generate sustainable economic development, followed by the environmental aspect and social aspects. The result of this paper is intended to increase awareness of people for geological and mining heritage as a valuable site for geotourism objects.